Evaluation The Effect of Three Types of Light Curing Systems On Temperature Rise intrapulpally and at the tooth surface during resin-based composite polymerization (Mustansiria Dental Journal, 2019)
Fifteen human premolar teeth freshly extracted were used. Standardized class V was prepared  on the buccal and palatal surfaces of each tooth, the teeth randomly divided into three groups according to the curing mode of composite resin: group I cured with quart-tungsten halogen, group II cured with Soft Start While group III cured with Plasma Arc. The increase in temperature internally (inside the pulp chamber) and externally (at the outer surfaces of the tooth) for each sample of the three groups was measured by using two K type  thermocouple connected with electrical thermometer. Results: revealed a very high significant  differences (P= 0.0001) among the three groups . Conclusion: Plasma Arc  light curing unit showed significantly the highest increase in temperature, while the Soft Start gave lower value and Quartz Tungsten Halogen unit with lowest  temperature rise internally and externally.